Guy Vernon : A Novelette in Verse - Trowbridge, J. T. (John Townsend), 1827-1916 (Book collections on Project MUSE., 2012)
Edited and extensively annotated by the renowned poet and critic William Logan, this edition of Guy Vernon incorporates revisions Trowbridge marked in his own copy of the anthology. Back in print for the first time since 1878, the long seriocomic work about race, racism, and sexual intrigue in antebellum America reemerges as a lost classic of American literature.